Ukraine was Born Free and is Everywhere in Chains: Zakon bozhyi and Enlightenment. (3rd July 2021) - Powell, Sara Jo
ABSTRACT: This article examines the intellectual foundations of the Zakon bozhyi, an allegorical poem produced by the Brotherhood of Saints Cyril and Methodius in the mid-nineteenth century. The work is most often understood as a product of Romanticism. This article argues that it is rather a product of synergistic Enlightenment and Romantic thought. It focuses on the depiction of religion in the Zakon and demonstrates that depiction's origin in the Enlightenment. The article argues that work demonstrates a societal view of religion. Further, it demonstrates that the ecumenical stance of the Zakon is founded in the necessity for national and international stability, rather than in personal conviction. It emphasizes the importance of culturally specific forms of the Enlightenment, and shows how the Zakon is a product of a particularly East Slavic presentation of the movement.